Diagnosis of Tumours at Crossroads- Histopathology or Genetics in the Diagnosis of Breast Cancer: A Sri Lankan Perspective - Wijesinghe, H. (Faculty of Medicine, University of Colombo, 2020)
The diagnosis of breast carcinoma has evolved over the last two centuries from a post-morterm diagnosis based on macroscopy ...
Keywords: Tumours; Breast Cancer; Sri Lanka